Kenya agricultural policy profile - Laichena, Joshua; Kiptoo, E.; Nkanyani, S.; Mwamakamba, Sithembile; Jacobs-Mata, Inga; Ires, Idil (International Water Management Institute (IWMI), 2022)
This paper aims to provide an overview of Kenyan policies related to agriculture and climate change adaptation and mitigation in preparation for the Kenya National Policy Dialogue on 12 November 2022 in Nairobi, Kenya. The Dialogue is a joint programme with CGIAR Initiative on Diversification of East and Southern Africa led by International Water Management Institute (IWMI) Southern Africa, the Food, Agriculture and Natural Resources Policy Analysis Network (FANRPAN) South Africa, and the Kenya Institute for Public Policy Research and Analysis (KIPPRA) Kenya. The paper provides an overview of the economic and administrative profile of the country and general overview of the country’s economic status and agricultural and climate change policies that will be critically debated during the Dialogue.